Differential contribution of pyruvate carboxylation to anaplerosis and cataplerosis during non-gluconeogenic and gluconeogenic conditions in HepG2 cells - Siriluck Wattanavanitchakorn (2020)
© 2019 Elsevier Inc. Pyruvate carboxylase (PC) is an anaplerotic enzyme that supplies oxaloacetate to mitochondria enabling the maintenance of other metabolic intermediates consumed by cataplerosis. Using liquid chromatography mass spectrometry (LC-MS) to measure metabolic intermediates derived from uniformly labeled 13C6-glucose or [3–13C]L-lactate, we investigated the contribution of PC to anaplerosis and cataplerosis in the liver cell line HepG2. Suppression of PC expression by short hairpin RNA lowered incorporation of 13C glucose incorporation into tricarboxylic acid cycle intermediates, aspartate, glutamate and sugar derivatives, indicating impaired cataplerosis. The perturbation of these biosynthetic pathways is accompanied by a marked decrease of cell viability and proliferation. In contrast, under gluconeogenic conditions where the HepG2 cells use lactate as a carbon source, pyruvate carboxylation contributed very little to the maintenance of these metabolites. Suppression of PC did not affect the percent incorporation of 13C-labeled carbon from lactate into citrate, α-ketoglutarate, malate, succinate as well as aspartate and glutamate, suggesting that under gluconeogenic condition, PC does not support cataplerosis from lactate.